The Relevancy of Teaching Method in Teaching Reading Comprehension with Syllabus and Lesson Plan A Case Study in Junior High Schools in Perbaungan. - Tampubolon, Menry Tampubolon (Journal of Applied Linguistics, 2021)
This study aims to describe the relevancy of teaching method in teaching Reading Comprehension with Syllabus and Lesson Plan in Junior High Schools in Perbaungan. The relevance that used is the relevance of an assumption to a context. The subjects of this study are the five English teachers of four Junior high Schools in Perbaungan. The instruments for collecting data used are : observations, treatment and the method of this study is qualitative research method. The data was taken after giving treatment. After conducting the research, it was found that two teachers used KWL Method in teaching Recount text, one teacher used PORPE Method in teaching Narrative text and they applied their teaching methods in teaching learning process in teaching Reading Comprehension are relevance with Lesson Plan and Syllabus result the students’ achievement in reading comprehension is high and above KKM ( Kriteria Ketuntasan Minimal / Minimal Completeness Criteria), one teacher applied his teaching method in teaching learning process in teaching Reading Comprehension is not relevance with Lesson Plan and Syllabus and one teacher did not apply a teaching method in teaching learning process in teaching Reading Comprehension. Key words : Relevancy, Teaching Method in Teaching Reading Comprehension, Syllabus, Lesson Plan.